1990
DOI: 10.1007/bf01786888
|View full text |Cite
|
Sign up to set email alerts
|

Effects of opioid peptides on the cellular immunity in spleen cells from intact nude mice or nude mice bearing human ovarian carcinoma

Abstract: The present study was designed to explore the effects of opioid peptides on the lytic activity of spleen cells from intact nude mice or nude mice bearing human ovarian cancer cells (KF). When the spleen cells from intact nude mice were incubated with various concentrations of opioid peptides, the ability of the spleen cells to lyse the KF cells was significantly stimulated between 0.05 nM and 50 nM concentrations of all opioid peptides used in this study. The degree of stimulation was most marked at 5 nM opioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…It has been shown that met-enkephalin inhibits in vitro proliferation of human cancer cells [42] and enhances the ability of the intact nude mice splenocytes to lyse human cancer cells [43]. In addition met-enkephalin inhibits tumor growth in animal transplanted with human tumor cell [44] and suppresses tumor metastasis in mice [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that met-enkephalin inhibits in vitro proliferation of human cancer cells [42] and enhances the ability of the intact nude mice splenocytes to lyse human cancer cells [43]. In addition met-enkephalin inhibits tumor growth in animal transplanted with human tumor cell [44] and suppresses tumor metastasis in mice [45].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a total reduction in opioid receptors of tumor bearing mice lymphocytes, but do not elucidate which receptor decreases and which one doesn't change. Opioid receptors on immune cells mediate anti-tumor activities of endogenous opioid peptides [43][44][45], thus determination of opioid receptor level on immune cell subpopulation in a cancer patient with different tumor origin further reveals any possible defect in immune function in response to tumor, hence we can design a better treatment regimen for cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 1989, Kikuchi and colleagues [27] reported that β-endorphin, α-endorphin, and [Met 5 ]-enkephalin 1) inhibited the growth of human serous cytoadenocarcinoma cells of the ovary in vitro in a dose-dependent manner that was partially reversed by the opioid antagonist, naloxone, and 2) decreased protein and RNA synthesis but not DNA synthesis as measured by [ 3 H]thymidine incorporation over a 48 h period of time. In a subsequent study, Kikuchi et al [28] noted that β-endorphin (but not α-endorphin or [Met 5 ]-enkephalin) increased lytic activity in spleen cells from mice bearing human ovarian carcinoma, and speculated that opioid peptides play a role in immune surveillance mechanisms. Finally, Mollick et al [29] reported antibodies to OGFr in the serum of 4 ovarian cancer patients, and suggested that OGFr may be a "useful target for vaccination".…”
Section: Introductionmentioning
confidence: 99%
“…It is known that NDV-infected lympocytes produce ACTH and endorphins [161]. Effects of opioids on lymphocytes are stimulatory and intensifying to cytotoxicity [162], except when the effect is continuous: then this stimulation is abolished [163]. This limited number of examples is cited here to raise the point that transfected viral genes should be able to encode biologically active proteins, and by selecting the transfected gene single reactions or cascades of reactions leading to the desired effect may be induced.…”
Section: Transfection O F Cancer Cells With Genes Encoding Selected Vmentioning
confidence: 99%